Proceso atención de enfermería en pre-escolar con depleción de volumen e hipertermia idiopática. - Tapia Sánchez, Odalys Birmania (2022)
Volume depletion is conceptualized as the loss of extracellular fluid volume, this anomaly is caused by total shortages of body contents such as water, sodium, potassium, among other electrolytes. It is particularized by the clinical manifestations of decreased skin moisture, mucous membranes become dehydrated due to fluid loss, tachycardia is originated. Hyperthermia is caused by variation or malfunction in thermoregulation in a hypothalamic disorder, based on not responding to drugs and presenting with severity, several syndromes are linked to a variation of body temperature in an individual. The present clinical case study is based on a patient with a clinical picture of gastroenteritis + volume depletion, which had as its main objective to apply the nursing care process, where due care was applied, application of interventions based on the theories of M. Gordon, NANDA, NICDA, and NICU. Gordon, NANDA, NIC and NOC theories, once the complementary tests were applied and the results were analyzed, the specific treatment to treat the clinical picture was determined, in conclusion, it was possible to determine the severe degree of volume depletion, in which the nursing administered the corresponding hydration and control the depletion picture that complicated the situation and the patient's health perception. The nursing staff was able to carry out care interventions in preschool patients with volume depletion and idiopathic hyperthermia.